The influence of personality traits on adolescent alcohol consumption trends - Rus, Mihaela; Sandu, Mihaela Luminita; Rus, Ciprian Vasile (Technium Social Sciences Journal, 2021)
Adolescence is assessed differently is being called the golden age, ungrateful, great elanuri, drama, crisis, anxiety, insecurity, social integration. Gradually, mental development, especially the intellect is mature in relation to social and cultural make it more accountable. It dominates the living new experiences and tend to self assertion expressions of disdain for the family because the teenager begins to believe that it is in adulthood. Alcohol use in adolescents, personality traits and the factors that determine consumption (psychological, hereditary and environmental, social and environmental), represented in particular by the groups entourage who are trained in adolescents, the subject of this research.